Radiation Exposure to the Thyroid After the Chernobyl Accident - Drozdovitch, Vladimir (Frontiers in Endocrinology, 2021)
Introduction: The accident at the Chernobyl nuclear power plant in Ukraine on 26 April 1986 resulted in a considerable release of radioactivity to the atmosphere, particularly of Iodine-131 (131I), with the greatest contamination occurring in Belarus, Ukraine, and western part of Russia. Material and Methods: Increase in thyroid cancer and other thyroid diseases incidence in exposed population in these counties was the major health effect of Chernobyl accident. Therefore, a lot of attention was paid to the thyroid doses, mainly, the 131I intake during two months after the accident. This paper reviews thyroid doses, both the individual for the subjects of radiation epidemiological studies and population-average doses. Exposure to 131I intake and other exposure pathways to population of affected regions and the Chernobyl cleanup workers (liquidators) are considered. Results: Individual thyroid doses due to 131I intake varied up to 42 Gy and depended on the age of the person, the region where a person was exposed, and their cow’s milk consumption habits. Population-average thyroid doses among children of youngest age reached up to 0.75 Gy in the most contaminated area, the Gomel Oblast, in Belarus. Intake of 131I was the main pathway of exposure to the thyroid gland; its mean contribution to the thyroid dose in affected regions was more than 90%. The mean thyroid dose due to 131I inhalation by early Chernobyl cleanup workers was estimated to be 0.18 Gy. Individual thyroid doses due to different exposure pathways varied among cleanup workers included in the epidemiological studies up to 9 Gy. Uncertainties associated with dose estimates, in terms of mean geometric standard deviation of individual stochastic doses, varied in range from 1.6 for doses based on individual-radiation measurements to 2.6 for ‘modelled’ doses. Conclusion: From the radiological point of view, the 131I was the most important radionuclide that resulted in radiation exposure to the thyroid during the first few weeks after the Chernobyl accident and cause an increase in the of rate of thyroid cancer and other thyroid diseases in exposed population.